Clinical outcomes of stereotactic magnetic resonance image‐guided adaptive radiotherapy for primary and metastatic tumors in the abdomen and pelvis. (20th July 2021) - Yoon, Stephanie M.; Luterstein, Elaine; Chu, Fang‐I; Cao, Minsong; Lamb, James; Agazaryan, Nzhde; Low, Daniel; Raldow, Ann; Steinberg, Michael L.; Lee, Percy
Abstract: Purpose: Stereotactic body radiotherapy (SBRT) delivers ablative doses with excellent local control. However, implementing SBRT for abdominal and pelvic tumors has been limited by the risk for treatment‐related gastrointestinal toxicity. MRI‐guided radiotherapy may ameliorate these risks and increase the therapeutic ratio. We report the clinical outcomes of stereotactic MRI‐guided adaptive radiotherapy (SMART) for primary and metastatic tumors in the abdomen and pelvis. Methods: From November 2014 to August 2017, the first 106 consecutive patients with 121 tumors in the abdomen and pelvis were treated with SMART at a single institution. Of the cohort, 41.5%, 15.1%, and 43.4% had primary, locally recurrent, and oligometastatic tumors, respectively. SMART was delivered using a tri‐cobalt‐60 gantry with on‐board 0.35 Tesla MRI with respiratory breath‐hold and daily adaptive re‐planning when anatomically necessary. A median of 40Gy in five fractions was prescribed. The Common Terminology Criteria for Adverse Events v.4.03 was used to score treatment‐related toxicities. Local control (LC), progression‐free survival (PFS), and overall survival (OS) were estimated using Kaplan–Meier method. Results: Of the 510 treatments, seventy‐one (13.9%) were adapted. Fatigue, nausea, and pain were the most common acute toxicities. 0.9 and 0% of patients experienced acute grade three and four toxicities, respectively. 5.2 and 2.1% of patients experienced late grade three and four toxicities, respectively. After a median follow‐up of 20.4 months, the 2‐year LC rate was 74% on a per‐lesion basis. Two‐year LC was 96% for lesions that were treated with BED10 ≥100 versus 69% for BED10 <100 ( p  = 0.02). PFS was significantly different between patients with and without locally controlled tumors (2‐year PFS 21 vs. 8%, p  = 0.03). Two‐year OS was 57% for the entire cohort. Conclusions: Favorable LC and PFS outcomes were observed with minimal morbidity for tumors in the abdomen and pelvis treated with SMART. Future prospective clinical trials to validate these findings are warranted. Abstract : Implementing stereotactic body radiotherapy for abdominal and pelvic tumors has been limited by risk for treatment‐related gastrointestinal toxicity. In the largest reported clinical series to date of stereotactic magnetic resonance image‐guided adaptive radiotherapy, favorable local control and progression‐free survival were observed with minimal morbidity.